Answer:
x = 9
Explanation:
Start by dividing both sides by the singular number, 3. We divide by 3 and not 21 because 21 is the result of the equation, not the coefficient.
![(3\left(x-2\right))/(3)=(21)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/caviys6t5myml5s9jyoran07x1sw8qqy1r.png)
We got 21 over 3 because you cannot divide 3 times an unknown number subtracted by 2 by 3. This is because we do not know the number. So that's where 21 comes in.
Next, simplify this equation by dividing whole numbers.
![(3)/(3) = 1](https://img.qammunity.org/2023/formulas/mathematics/high-school/gyr664ep24i1st8k7vplofhaq9gufd1850.png)
![1\left(x-2\right) = \left(x-2\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/f3f7xo5uxv3cl1h33fzoblxbq7dydkpjrp.png)
![(21)/(3) = 7\\= x-2 = 7](https://img.qammunity.org/2023/formulas/mathematics/high-school/fuwfvxe2q5zfxmd2ubnt66chqh5rgvg5nl.png)
Lastly, add 2.
![x - 2 + 2 = 7 + 2\\2 + 2 = 4\\7 + 2 = 9\\= x - 4 = 9\\x = 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/1dstn7jrm46uc55c6e581vcuawy8v6qjjj.png)
Why x - 4 is 0: We assume x is always equal to 1, since 4 does not go into 1, the result would be 0. x - 0 = 0. Therefore, the problem became x = 9.
Hope this helps!